Radiological diagnosis of Coronavirus Disease 2019 (COVID-19): a Practical Guide - Floridi, Chiara; Fogante, Marco; Agostini, Andrea; Borgheresi, Alessandra; Cellina, Michaela; Natella, Raffaele; Bruno, Federico; Cozzi, Diletta; Maggialetti, Nicola; Palumbo, Pierpaolo; Miele, Vittorio; Carotti, Marina; et al. (Acta Biomedica Atenei Parmensis, 2020)
Novel beta-coronavirus (2019-nCoV) is the cause of Coronavirus disease-19 (COVID-19), and on March 12th 2020, the World Health Organization defined COVID-19 as a controllable pandemic. Currently, the 2019 novel coronavirus (SARS-CoV-2) can be identified by virus isolation or viral nucleic acid detection; however, false negatives associated with the nucleic acid detection provide a clinical challenge. Imaging examination has become the indispensable means not only in the early detection and diagnosis but also in monitoring the clinical course, evaluating the disease severity, and may be presented as an important warning signal preceding the negative RT-PCR test results. Different radiological modalities can be used in different disease settings. Radiology Departments must be nimble in implementing operational changes to ensure continued radiology services and protect patients and staff health.